(3GdMLI hGdHQgGf Ydi aJjGf gPG GdReGfs - (3GOQjS Hf HjQ jcjf Hf YHO Gddg GdJQceGfj GdMfajs
(3ChdgG (B:s
(3bGd SHMGfg Efge aJjI BefhG HQHge hROfGge s
(3BNQgG (B:s
(3hGdJNdb HGdCNdGb GdLejdI hGLJfGH cd QPjdI hGdbjGe HMbhb GdENhGf hMSHfG Gddg SHMGfg hcai s
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B631s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3aQhSjI JjehQ (B64) s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs